TÓPICOS DO ELETROMAGNETISMO ABORDADOS COM UMA SEQUÊNCIA DIDÁTICA EXPERIMENTAL PARA UMA APRENDIZAGEM SIGNIFICATIVA NO ENSINO MÉDIO. - ROSAS, Ajax Wellington Parente (2020)
This work proposes the implementation of a Didactic Sequence (SD) that integrates the application in the classroom of the use of materials of easy access and of low cost to the teachers and students, in order to promote a meaningful learning. With the objective of providing a change in the reality of the school environment, this study sought to transform physical phenomena into interesting contents, leaving the conceptual scope for the practicality of the experimental, thus allowing the construction of knowledge in a meaningful way that inserts the student in the context of the discussion effectively. In a qualitative and quantitative research, in a case study, in an environment of a state public school in the city of São Luís / MA, a didactic sequence of ten meetings was applied, using diversified activities that involved a questionnaire to evaluate previous knowledge. , dialogue lectures, concept maps and experimental activities with low-cost materials. The Didactic Sequence is based on the Theory of Meaningful Learning, in which the learning characterized by the interaction between previous knowledge and the new knowledge reached a greater meaning in the students' cognitive structures. In the approach, he was concerned with clarifying magnetic phenomena in different contexts and their relationship with our daily lives. Thus, after the application of the didactic sequence to the students of the 3rd Grade of High School, it was found that the activities enabled the exercise of conceptual, procedural and attitudinal contents, for a meaningful learning related to Electromagnetism. In addition, the assessment, which is an essential part of the teaching and learning process, was carried out throughout the work and always considering the responses of the students, as they reached the proposed pedagogical objectives. As a result, graphics with the diagnostic evaluation on Electromagnetism are displayed, texts produced by the students that reflect the formative evaluations and photos that demonstrate the effective participation of the students in the assembly and exhibition of the experiments made during the development of the didactic sequence. With the above, it allows us to evaluate that this work reached its objective and contributed to an effective participation of the students participating in the construction of knowledge and led them to a significant learning of the conceptual, procedural and attitudinal contents on topics of Electromagnetism. The results of this research culminated in the construction of an educational product aimed at teachers and high school students.